Pengembangan Puzzle Game Tentang Keragaman Budaya Indonesia Berbantuan Interactive Whiteboard - Amelia Bella Satya Yuda; I Nyoman Sudana Degeng; Yerry Soepriyanto (Universitas Negeri Malang, 2020)
Abstract: The aim of this research is to produce a puzzle game about Indonesian culture product assisted by an interactive whiteboard that attracts students' attention, fosters learning motivation, is interactive, is fun, and students are directly involved in learning and are valid or appropriate for use in learning. Submission of material is packaged in an educational game in the form of dialogue, mission, challenges, and obstacles and when played by students will automatically learn about the diversity of Indonesian culture. This study uses a multimedia development model according to Lee & Owens with three stages of completion, that is assessment/analysis, design dan development. The result of the development puzzle game about Indonesian culture assisted by Interactive Whiteboard has received positive responses from media experts and material experts and is appropriate to use.Abstrak: Tujuan dari pengembangan ini adalah menghasilkan produk Puzzle Game Keragaman Budaya Indonesia berbantuan interactive whiteboard yang menarik perhatian siswa, menumbuhkan motivasi belajar, interaktif, menyenangkan dan siswa terlibat langsung dalam pembelajaran yang layak untuk digunakan. Penyampaian materi dikemas didalam game edukasi berupa dialog, misi, tantangan dan hambatan dan ketika dimainkan oleh peserta didik otomatis akan belajar tentang keragaman budaya Indonesia. Penelitian ini menggunakan model pengembangan multimedia menurut Lee & Owens dengan tiga tahap penyelesaian, yaitu assessment/analysis, design dan development. Hasil pengembangan adalah Puzzle Game Keragaman Budaya Indonesia berbantuan Interactive Whiteboard mendapatkan respon positif oleh ahli media dan ahli materi serta layak digunakan.